STRATEGI KEPEMIMPINAN KEPALA SEKOLAH BERBASIS MULTIKULTURAL UNTUK MEMBENTUK KARAKTER PESERTA DIDIK PADA JENJANG SEKOLAH DASAR - Hadya Salsabila; Raden Muhammad Jallaludin Assayuti; Salsabila Khalishah Fitri; Novan Ardy Wiyani (CV. Adiba Aisha Amira, 2025)
In the context of basic education, multiculturalism plays an important role in shaping the character of students who are tolerant, open, and respectful of differences. This study aims to analyze the leadership strategies of multicultural-based school principals in shaping the character of students in elementary schools. The focus of the research is directed at how school principals integrate multicultural values into the learning process, extracurricular activities, and school culture. This research uses a qualitative approach with a library research method, where data is obtained from various literature sources such as books, scientific journals, and relevant research results. The research results show that the principal has a central role in creating an inclusive, equitable and diversity-respecting learning environment. The strategies used include integrating multicultural values into the curriculum, strengthening the role of teachers through training, developing diversity-based extracurricular activities, and establishing a school culture that fosters attitudes of tolerance and empathy. These findings underscore the importance of principal leadership as an agent of change in realizing humanistic and socially just basic education. Multicultural education in elementary schools contributes significantly to the development of students' character, who are moral, respectful of differences, and able to live harmoniously in a diverse society.